The midnight library - Haig, Matt (Canongate, 2021)
Nora's life has been going from bad to worse. Then at the stroke of midnight on her last day on earth she finds herself transported to a library. There she is given the chance to undo her regrets and try out each of the other lives she might have lived. Which raises the ultimate question: with infinite choices, what is the best way to live?